Utilization of Preventive Care Visits in Primary Healthcare: Evidence from Indonesia’s National Health Insurance - Hasibuan, Syarif Rahman (Jurnal Jaminan Kesehatan Nasional, 2025)
Visiting primary health care providers for preventive care services is vital for early disease detection and overall population health improvement. In Indonesia, various barriers such as financial, systemic, and social, contribute to the underutilization of preventive health visits. This analytic cross-sectional study analyzed secondary data from a 1% representative sample of Indonesia’s National Health Insurance (JKN) participants in 2023, including 608,572 individuals who had accessed at least one healthy visit at a primary care facility between 2017 and 2023. Descriptive statistics and a Generalized Linear Model assessed associations between healthy visit utilization and sex, generation, residence, and JKN membership segment. Utilization was higher among participants living in urban areas, government-subsidized members, non-workers, and older generations (particularly Baby Boomers), whereas the lowest rates were observed among informal workers, post-millennials, males, and participants residing in rural regencies. All associations were statistically significant (p < 0.01). These findings highlight significant disparities in healthy visit utilization across demographic and insurance groups in Indonesia’s National Health Insurance program. Targeted interventions to increase preventive care uptake among underrepresented populations are critical to achieving equitable health outcomes.